Experimental Study of The Addition of Palm Fiber (Arenga Pinnata) as Fiber Against The Compressive Strength of Pozzolan Bricks - Mahdika Putra Nanda (Jurnal Teknik Sipil dan Perencanaan)
Abstract. Brick is a building material widely used as a construction material for walls and fences, one of which uses Pozzolan brick. Pozzolan brick is made from Trass, lime, or cement. A local material that can be used as an additional fiber in the mixture of Pozzolan brick making is fibers, because it has been proven that the addition of fibers in concrete can improve its physical and mechanical properties, in addition, the fibers also have a hard rotten nature because there is no decomposer that can decompose them. Thus, it is necessary to investigate the addition of fibers as fiber in Pozzolan bricks. The experimental method was used in this study. The purpose of this study is to find out whether Pozzolan bricks with the addition of a mixture of fibers have better compressive strength and to find out whether they meet the requirements to become bricks according to SNI 15-2094-2000 and PUBI-1982. From the results of research and analysis that has been done regarding the addition of fiber fibers (Arenga pinnata) as a fiber to the compressive strength of pozzolan bricks, it is found that the compressive strength of pozzolan is 4.99 Mpa with a porosity value of 3.24%, thus pozzolan bricks can provide economic value for the wider community. Based on the compressive strength and porosity, pozzolan bricks also meet the requirements to become bricks according to SNI 15-2094-2000 and PUBI-1982 in grade III.